2014
DOI: 10.1176/appi.ajp.2014.13091198
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Preschool Disorders to Full DSM Depression at School Age and Early Adolescence: Continuity of Preschool Depression

Abstract: Background Preschool-onset depression, a developmentally adapted form of depression arising between the ages of 3–6, has demonstrated numerous features of validity including characteristic alterations in stress reactivity and brain function. Notably, this validated syndrome with multiple clinical markers is characterized by sub-threshold DSM Major Depressive Disorder criteria, raising questions about its clinical significance. To clarify the utility and public health significance of the preschool-onset depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
135
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 36 publications
10
135
4
1
Order By: Relevance
“…Thus, research with substantially larger samples is required to determine whether objectively measured MVPA would decrease the risk of MDD in community children. Nonetheless, because previous research has shown that there is a continuity in depressive symptoms from childhood to adolescence and later adulthood, 53 that an elevated level of MDD symptoms increases the risk of later MDD, 54,55 and that subclinical depression may entail substantial impairment (also in the long run), 56 our findings suggest that increasing MVPA at the population level may lead to reduced symptoms of depressionand the impairment that accompanies these symptoms in some children. Second, data were MNAR, which may have led to biased results.…”
Section: Limitationsmentioning
confidence: 60%
“…Thus, research with substantially larger samples is required to determine whether objectively measured MVPA would decrease the risk of MDD in community children. Nonetheless, because previous research has shown that there is a continuity in depressive symptoms from childhood to adolescence and later adulthood, 53 that an elevated level of MDD symptoms increases the risk of later MDD, 54,55 and that subclinical depression may entail substantial impairment (also in the long run), 56 our findings suggest that increasing MVPA at the population level may lead to reduced symptoms of depressionand the impairment that accompanies these symptoms in some children. Second, data were MNAR, which may have led to biased results.…”
Section: Limitationsmentioning
confidence: 60%
“…Modal onset of first episodes of depression most commonly occur in middle to late adolescence (1, 2), and many adult depressive episodes represent recurrences of adolescent-onset depression (3). Compelling evidence shows that depression often begins much earlier than previously believed, including during preschool (4,5). Risk factors and processes first emerge, and then accumulate and crystalize over time, likely via dynamic developmental cascades starting with early adverse environments and then ongoing chronic and acute stressors that transact with these vulnerabilities across multiple systems and levels of analysis until these risks stabilize and consolidate.…”
mentioning
confidence: 93%
“…Some symptoms assessed by this scale (such as irritability and loneliness) cut across multiple diagnostic categories, and indeed, scores on the depression subscale were correlated with reports of overall externalizing symptoms; it is unclear whether this simply reflects the high comorbidity among emotional and behavioral diagnoses or a more critical measurement issue. Some researchers have found that current diagnostic criteria (used for children and adults) can be used to adequately assess depression in preschoolers (see Luby et al, 2014) and distinguish depression from certain behavioral disorders (Strickland et al, 2011); however, this research area is still in its infancy, and it is crucial that we learn more about how these symptoms develop and manifest themselves in very young children to aid early intervention efforts. Fifth, the study did not evaluate possible mechanisms of the link between fathers’ and children’s depression, such as parenting or family conflict.…”
Section: Discussionmentioning
confidence: 99%
“…One-year prevalence rates for MDD have been estimated at about 2% for children and 4–7% for adolescents (Costello et al, 2002), and approximately 15–20% of teenagers will experience MDD by the time they reach 18 years of age (Birmaher et al, 1996). Several researchers have found that children who experience depressive symptoms are at significantly higher risk for experiencing depression later in life (e.g., Harrington, Fudge, Rutter, Pickles, & Hill, 1990; McGee & Williams, 1988), and even depressive symptoms in preschool (assessed at ages 2–5) have been found to predict higher levels of depression and other internalizing problems several years later (Lavigne et al, 1998; Luby, Gaffrey, Tillman, April, & Belden, 2014; Mesman & Koot, 2001). …”
mentioning
confidence: 99%